If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3 = 12 + -1x Reorder the terms: -3 + 4x = 12 + -1x Solving -3 + 4x = 12 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -3 + 4x + x = 12 + -1x + x Combine like terms: 4x + x = 5x -3 + 5x = 12 + -1x + x Combine like terms: -1x + x = 0 -3 + 5x = 12 + 0 -3 + 5x = 12 Add '3' to each side of the equation. -3 + 3 + 5x = 12 + 3 Combine like terms: -3 + 3 = 0 0 + 5x = 12 + 3 5x = 12 + 3 Combine like terms: 12 + 3 = 15 5x = 15 Divide each side by '5'. x = 3 Simplifying x = 3
| 15y-4=60-y | | 3x-7=4x+18 | | 10-3(1-7x)=-4x-8 | | (3+7i)+(6-5i)= | | 22-42=4(x-1)4 | | 6p-15=3p | | (2x)2+14=78 | | (-2/3)14c=(2/3) | | 4-2(5+4x)=-x+1 | | 3(3x-4)=x(32)-22 | | 4-2(10n-6)=10(-2n+7)+4 | | 15y-4=60y | | (7i)(3i)= | | 49x^2+1+14x= | | 2x-27=23 | | -2x=2y-8 | | -11g=7(1-2f)+5 | | 20m=15 | | 3b/a-5/7 | | 3+16x=-15 | | 5x-4=4-3(5-2x) | | -26=4x-9 | | 21=15a | | 43-2x=-8x | | 3x+1=79 | | 2h+h= | | 5x=297 | | 4x-5=11x-70 | | 8m-(7+5m)= | | x/2-10=x-32 | | http://x/2-10=x-32 | | x^3=96 |